Cardiovascular Surgical practice at National Heart Centre: where do we stand? - Acharya, A; Rai, K; Sharma, P; Pradhan, S; Sharma, J; Koirala, RR; Koirala, B (Nepalese Heart Journal, 2004)
Here we present the overview of cardiovascular surgeries performed at SGNHC from its commencement in August 2001 to January 2004 at SGNHC. We retrieved the data from the hospital records of all these patients and were analyzed for age, sex, preoperative condition, type of surgery, ICU stay, post operative hospital stay and mortality.